OECD average annual hours worked: Comparative analysis and implications - MinSub Kim (Korea Development Institute (KDI), 2023)
The OECD statistics on annual hours worked per person are often cited as evidence for Korea's long working hours, but this in fact tends to be the result of the nation's high proportion of self-employed workers and low proportion of part-time workers. When this distinct employment composition is taken into account, the difference between Korea's hours worked and those of other OECD countries turns out to be much less significant compared to previous estimates. However, Korea's hours worked do remain relatively longer even after such an adjustment. Therefore, it is important to figure out and thereby address underlying institutional factors of unproductive long working hours. Furthermore, flexible and choice-based working arrangements should be promoted for improving labor market efficiency.
Keywords: 330